A fresh look at an old question: is pro-poor targeting of cash transfers more effective than universal systems at reducing inequality and poverty? - ImPRovE, Antwerp; McKnight, Abigail (Antwerp, 2015)
"This paper presents findings on the changing effectiveness of cash transfers and income taxes on inequality and poverty reduction in four EU countries – the UK, Italy, Sweden and France. We use long time series (spanning four decades) to examine trends within countries over time and between countries at different points in time. Recent evidence has suggested that the relationship between concentration of cash transfers and their redistributive effectiveness has become blurred over time. We find much more conclusive evidence of a negative relationship within countries over time. The results show a negative relationship between the concentration of cash transfers net of direct taxes and their effectiveness in terms of reducing poverty and inequality. The strength of the relationship varies between countries and in some cases between the all age and the working age populations. The evidence suggests that caution should be applied to relying on bivariate cross-country estimates and that more should be done to establish and verify empirical relationships within countries over time using the rich data sources that are now available. These findings re-open the debate on the most effective design of cash transfer and direct tax systems."